The role of Tru-cut needle biopsy in the diagnosis of palpable breast masses. - Hassan, Mahmood H.; Hizam, Ahmed R.; Al-Obaidi, Safa M. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Breast Lump Is The Second Most Common Presenting Symptom, After Breast Pain, To The Breast Clinic. Tru-Cut Needle Biopsy Provides Enough Tissue For Histopathological Diagnosis And Is Considered A Reliable Method For Establishing Preoperative Tissue Diagnosis. Objectives: To Compare The Results Of Fine Needle Aspiration Cytology (FNAC), Tru-Cut Needle Biopsy With Excisional Biopsy In Detecting Breast Cancer In Palpable Breast Masses. Results: This Study Shows That Tru-Cut Needle Biopsy Is Superior To FNAC In Confirming Breast Cancer In Palpable Breast Masses With Suspicion Of Malignancy And It Can Give Definitive Histopathological Diagnosis Of The Lesion With Low Cost And Low Complication Rate.Patients and Methods: This Is A Prospective Study Done In Baghdad Teaching Hospital Breast Clinic From January 2009 To October 2010.It Is Conducted On 120 Females Who Presented With Palpable Breast Masses. After Detailed History And Physical Examination The Patients Were Sent For Ultrasound Examination And/Or Mammography And Then Both FNAC And Tru-Cut Needle Biopsy Were Performed In An Outpatient Setting Followed By Excisional Biopsy. Conclusion: Tru-Cut Needle Biopsy Is Superior To Fine Needle Aspiration Cytology In The Detection Of Breast Cancer In Palpable Breast Masses With Low Cost And Low Complication Rate.